2012
DOI: 10.1097/mcp.0b013e32834feb37
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism in chronic obstructive pulmonary disease

Abstract: The relationship between hypogonadism and COPD still remains poorly understood. The current literature is at best circumstantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 51 publications
0
63
0
Order By: Relevance
“…Previous studies have reported low T concentrations in men with COPD [24,25]. One cross-sectional study assessed FEV1, FVC and total T in 83 men with stable COPD, 20 with exacerbations of COPD and 30 age-matched controls [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported low T concentrations in men with COPD [24,25]. One cross-sectional study assessed FEV1, FVC and total T in 83 men with stable COPD, 20 with exacerbations of COPD and 30 age-matched controls [26].…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormone disturbances are common in COPD; a recent review estimated the prevalence of testosterone deficiency in male COPD patients between 22 % and 69 % [108]. The cause of this deficiency is multifactorial and it includes chronic hypoxia, disease severity, smoking, corticosteroid therapy, chronic inflammation and aging itself [109].…”
Section: Androgen Deficiencymentioning
confidence: 99%
“…The mechanism of hypogonadism in COPD was considered to be multifactorial and many factors such as aging, obesity, systemic inflammation, hypoxemia, hypercapnia, and administration of glucocorticoids were suggested to contribute toward the pathogenesis of such a condition [30,31]. Patients with severe disease in the present study had significantly lower total testosterone and FSH in comparison with their controls with normal pulmonary function, whereas patients with mild and moderate disease did not show such a decrease in the total testosterone level compared with their controls.…”
Section: Figurementioning
confidence: 99%
“…between the symptoms of LOH and symptoms of both aging and COPD, and will prevent overdescription of testosterone replacement therapy [30].…”
Section: Figurementioning
confidence: 99%